Enrobing Ceremony for Judges Thomas Harris, Steven Vartabedian, Edward Sarkisian, Jr. and Lawrence Jones at Fresno's Veterans Memorial Auditorium - Watkins, Howard::::::::: (1987)
Judge Robert Mardikian administering oath of office to Steven Vartabedian with his wife Marilyn and their three daughters Stefanie, Pamela and Melanie looking on